Pengaruh Gaya Kepemimpinan, Disiplin, Lingkungan Kerja, dan Kompensasi Terhadap Kinerja Karyawan PT Tasik Raja - Fitri Rahmayani Hasibuan; Abd. Halim; Nur’ainun Gulo (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of leadership style, work discipline, work environment, and compensation on employee performance at PT Tasik Raja Cikampak Labuhanbatu Selatan. The sample size was 100 respondents. This study uses validity test, reliability test, classical assumption test, multiple linear regression test, t test, F test, and coefficient of determination using SPSS 27. The study was conducted to examine how independent variables influence dependent variables and the percentage level of influence of research variables by distributing research questionnaires to respondents and conducting tests. The results showed that all independent variables influenced the dependent variable with all t count values> t table and significance values ​​<0.05 with a determination level of 0.655 or 65.50% giving a positive and significant influence.